RETRIBUSI PELAYANAN KEBERSIHAN DALAM PRINSIP GOOD GOVERNANCE - ", Nabilla; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Governance is everything that is related to actions or behaviors that are direct, controlling or influencing public affairs. As stated in the Pekanbaru Mayor Regulation Number 48 of 2016 concerning Management of Garbage / Cleaning Service Retribution. Management activities in the form of collecting cleaning service fees for the mandatory retribution (community). The purpose of this research is to be able to know and analyze the governance of waste / cleaning service fees in Pekanbaru City and to determine the inhibiting factors in the governance of cleaning service fees in Pekanbaru City. This study used purposive sampling technique with qualitative research using a phenomenological approach and the required data, both primary and secondary data, were obtained through observation, interviews and documentation and then analyzed based on the research problem. The results of this study indicate that the management of cleaning service fees in Pekanbaru City has not been running optimally. Inhibiting factors in the governance of cleaning service fees are human resources, facilities and infrastructure, as well as the application of legal sanctions.Keywords: Governance, Retribution.